The Role of MicroRNAs in Chronic Myeloid Leukemia (CML) Treatment, Biomarkers, and Resistance to Tyrosine Kinase Inhibitor: A Bioinformatics-Based Analysis: Role of MicroRNAs in Chronic Myeloid Leukemia (CML) Treatment - Mohamad, Syarifah Faezah binti Syed; Ramlee , Rabiatul Adawiyah; Elias, Marjanu Hikmah (Journal of Tropical Life Science, 2024)
Chronic myeloid leukemia (CML) is a myeloproliferative disorder caused by the reciprocal translocation of the BCR-ABL1 oncogene, which activates tyrosine kinase resulting in uncontrolled cell proliferation and apoptosis suppression. Although Imatinib (IM) is an effective treatment, IM resistance remains a significant concern. Therefore, microRNAs (miRNAs) have emerged as potential alternative therapies. These short, non-coding RNAs (20-22 nucleotides) regulate gene expression by binding to the 3' untranslated region (3'UTR) of target genes. The study aims to identify miRNAs linked to CML, determine miRNA’s target genes, construct a protein-protein interaction (PPI) network, and analyze pathways and gene ontology. A literature search using the keywords “microRNA”, and “chronic myeloid leukemia” yielded relevant papers, which were screened and categorized into three groups: 1) miRNA associated with TKI resistance, 2) miRNA as biomarkers or leukemogenesis, and 3) miRNA as therapy. Target genes for the identified miRNAs were determined using DIANA tools and miRTarBase. Gene ontology and pathway analysis were conducted using DAVID, while PPI and network visualization were performed using STRING, Cytoscape, and ClueGO. Thirteen miRNAs were selected, targeting 782 genes and forming 16 clusters. ClueGO identified clusters associated with key biological processes, including G1/S cell cycle transition, miRNA-mediated gene silencing, hematopoietic stem cell differentiation, and apoptosis regulation. Target genes are also significant in the CML pathway and other cancer pathways, such as p53, ErbB, FoxO, autophagy, apoptosis, VEGF, TNF, and microRNA. Notably, hsa-miR-16 emerged as the most promising therapeutic and biomarker candidate for CML, highlighting its role in critical pathways.